2021
DOI: 10.1186/s13104-021-05654-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nested-PCR and direct agglutination test (DAT) for the detection of Leishmania infantum infection in symptomatic and asymptomatic domestic dogs

Abstract: Objective Canine visceral leishmaniasis (CVL) is the main source of human visceral leishmaniosis (HVL) in Mediterranean region, including Iran and is spread from domestic dogs to Phlebotomine sand flies vectors to humans. To control the transmission of HVL, early and accurate detection of infected dogs is paramount importance despite it remains a confronting challenge. Herein, we evaluated the performance of direct agglutination test (DAT) against gold standard nested polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This study identified CL vectors using Nested-PCR. This method is widely used by many researchers in Iran and other countries as an alternative method for the detection of Leishmania and other protozoa (13,(20)(21)(22)(23)(24). Based on our findings, the prevalence of leishmaniasis has increased in Alborz province in recent years, which is consistent with the findings of previous studies in other regions (13,23).…”
Section: Discussionsupporting
confidence: 89%
“…This study identified CL vectors using Nested-PCR. This method is widely used by many researchers in Iran and other countries as an alternative method for the detection of Leishmania and other protozoa (13,(20)(21)(22)(23)(24). Based on our findings, the prevalence of leishmaniasis has increased in Alborz province in recent years, which is consistent with the findings of previous studies in other regions (13,23).…”
Section: Discussionsupporting
confidence: 89%
“…These data in humans were already highlighted in other studies [ 17 , 20 , 28 ]. Some studies found that age has an influence on asymptomatic status in humans [ 17 , 28 , 42 , 44 ]. The absence of differences regarding age in our human population may be explained by the median age of 52 years related to a rather long exposure to the bite of a potentially infected phlebotomine sand fly.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of CanL is complex, and it combines, besides compatible history and clinical signs, serological, molecular, and parasitological methods [7,29,[37][38][39]. Clinical staging, either following the LeishVet guidelines for the practical management of CanL [7] or the guidelines for the treatment of leishmaniasis in dogs [40], is also a very useful tool, especially during patient monitoring [41], as clinical evolution can have an impact on the prognosis and influence the efficacy of a particular treatment protocol.…”
Section: Canine Leishmaniosis and Associated Immune Responses 1canine Leishmaniosismentioning
confidence: 99%